En værkstruktur målrettet børn med Autisme Spektrum Forstyrrelse - Juhl Sørensen, Christine; Nymark, Anne (Peripeti, 2021)
This article presents our design process of a conceptual framework specially designed for children with Autistic Spectrum Disorder (ASD). We designed the conceptual framework for an interactive play called Race against time (I kapløb med tiden). In the article, we analyze the communication difficulties that may occur between theatrical elements and children with ASD, and discuss what kind of positive impact a theatrical concept may have on children with ASD when specially designed for that specific audience.